Biphasic effects of Callicarpa nudiflora water extract on rumen fermentation in vitro and microbial communities in sheep - Yang, Wanqin; Li, Runhang; Wang, Wenxi; Li, Kunna; Huang, Yiying; Ying, Ying; Liu, Yuning; Wu, Hongxin (Frontiers in Animal Science, 2025)
IntroductionThis study investigated the effects of varying doses of Callicarpa nudiflora water extract (CW) on in vitro rumen fermentation and sheep microbial activity.MethodsFour rumen-cannulated hybrid sheep were selected to provide mixed rumen fluid, and the powder substrate remained consistent with the diet fed to the sheep. A total of 14 supplementation levels (0–25 g/kg fresh substrate) of CW were designed based on a completely randomized design, including 0, 0.5, 1, 2, 3, 4, 6, 8, 10, 12, 14, 16, 20 and 25 g/kg. Each treatment was replicated in duplicate across three independent batches, resulting in a total of six biological replicates per treatment. The flasks were incubated at 39°C for 24 hours in water with a rotation speed of 80 r/min.ResultsIt showed that adding CW significantly affected in vitro rumen fermentation in sheep and displayed a biphasic action: The supplementation levels of 4 g/kg and 6 g/kg showed an improvement in the fermentation status and nitrogen utilization efficiency with the enhanced microbial protein concentration from 1.98 mg/mL (Con) to 2.84 mg/mL (P < 0.001) and the relative abundance of total bacteria from 4.05 (Con) to 5.27 (P < 0.001); When the dose surpassed 14g/kg, the decline in the hemicellulose degradation rate from 63.00% (Con) to 40.24% (P < 0.001), accompanied by an increase in ammonia-nitrogen (NH3−N) concentration from 173.37 mg/L (Con) to 177.46 mg/L (P = 0.020) and total gas production from 154.87 mL/g (Con) to 161.47 mL/g (P =0.007), signaled abnormal alterations in the fermentation process.Conclusions The optimal supplementation range in feed formulations was established as 4−6g/kg, showing that CW could serve as a natural rumen modulator for sheep.